Isotopic analysis in teeth of contemporary brazilians with known diet and geolocation and its forensic value for human identification (Research, Society and Development, 2021)
Dental anthropological data may provide valuable information about an individual's life, including age at death, health, signs of violence, ancestry, diet features, intentional modifications, and geographic origin. These pieces of information may be further detailed by diet and residential mobility estimates provided by isotopic analyses. The use of isotope data in the modern population is strongly dependent on the diverse origin of food supply, thus requiring an updated and location-specific database. In this study, we have analyzed the isotopic ratio of strontium, carbon, and nitrogen in enamel and dentin collagen of third molars individuals from three main cities in Brazil. Besides the isotope data, we have also surveyed their diet in adolescence habits to develop models to be applied for forensic studies in the Brazilian territory. We show that the forensic value of the place of origin estimation based 87Sr/86Sr levels is reduced in these highly urbanized samples. Among the outliers, most individuals are older than the mean age (25.1) or had water from wells in childhood. The sample's diet has a robust C4 presence and mean trophic levels consistent with the declared high frequency of chicken, meat, and dairy products, also compatible with the high consumption of sugar, rice, and beans in the local culture. Individuals with special diets, either by choice or therapeutic needs, were potential outliers among the group. Our results also contribute to the international human tissues isotopic database and can contribute for human identification of Brazilians or foreigners with distinct isotopic signatures.